Performance of pulmonary artery dimensions measured on high-resolution computed tomography scan for identifying pulmonary hypertension. Issue 1 (10th February 2020) - Ratanawatkul, Pailin; Oh, Andrea; Richards, J. Caleb; Swigris, Jeffrey J.
Background: On high-resolution computed tomography (HRCT), pulmonary artery (PA) dimensions may hint at the presence of pulmonary hypertension. We aimed to determine how accurately various measures of the PA, as viewed on HRCT, predict right heart catheterisation (RHC)-confirmed pulmonary hypertension. Methods: We retrospectively reviewed patients who had HRCT and RHC between 2010 and 2018. Analyses considered respiratory cycle, pulmonary hypertension diagnostic criteria, time between HRCT and RHC, and subgroup analysis in interstitial lung disease (ILD) and chronic obstructive pulmonary disease (COPD). Results: Of 620 patients, 375 had pulmonary hypertension. For pulmonary hypertension (defined as mean PA pressure (mPAP) ≥25 mmHg) and from HRCT performed within 60 days of RHC, main PA diameter (MPAD) ≥29 mm had a sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 88%, 42%, 0.70 and 0.70, respectively, while ratio of the diameter of the PA to the diameter of the ascending aorta (PA:Ao) ≥1.0 showed 53%, 85%, 0.84 and 0.54, respectively. In general, results were similar when the interval between HRCT and RHC varied from 7 to 60 days and when measured on expiratory images. In ILD, the sensitivity of MPAD was higher; in COPD, the specificity of PA:Ao was higher. There was moderately positive correlation between mPAP and inspiratory MPAD, PA:Ao, right PA diameter (RPAD), left PA diameter (LPAD) and (RPAD+LPAD)/2 (r=0.48, 0.51, 0.34, 0.34 and 0.36, respectively), whereas there was weak negative correlation between mPAP and PA angle (r= −0.24). Conclusions: Findings on HRCT may assist in the diagnosis of RHC-confirmed pulmonary hypertension. MPAD ≥29 mm had high sensitivity and PA:Ao ≥1.0 had high specificity. Compared with the entire cohort, MPAD had greater sensitivity in ILD and PA:Ao had higher specificity in COPD. Findings on HRCT may assist in the diagnosis of RHC-confirmed pulmonary hypertension. MPAD ≥29 mm has high sensitivity, whereas PA:Ao ≥1.0 has high specificity. MPAD has greater sensitivity in ILD and PA:Ao has higher specificity in COPD. http://bit.ly/2EcrEUY